Criticism of the Ideological Interpretation of the Concept of Democracy (Shura) in the Tafsir of Al-Wa'ie: Hermeneutic Analysis of Khaled Abou El-Fadl - Moh. Arif Rakman Hakim; Amir Bandar Abdul Majid (Spiritus: Religious Studies and Education Journal, 2024)
Democracy is an issue that is still popular for debate, especially as it is described in Islamic studies where Islam and democracy were born from different cultures of politics. This article used library research with an authoritative hermeneutical analysis by Khaled Abou El-Fadl. The objective of this article is to explain that the concept of democracy in general did not contradict the values of the Islamic tradition in the Quran.  In this article, it is clear and shown that Rokhmat S. Labib’s interpretation was included or categorized as an ideological interpretation. Labib stressed that democracy was a system that had to be banned because it contains aspects of secularism. He added that someone who follows the ideology of secularism is included in the category of kufr.  Based on Khaled Abou El-Fadl's hermeneutics, Labib's interpretation is categorized as authoritarian interpretation because Labib is more concerned with his ideology. Apart from that, Labib’s interpretation is very limited on writing his tafsir. In his writing, Labib just relies on limited reference and using some verses that support his ideology rather than comprehensively explain the context of the verses he interprets.  In the end, all the arguments in Labib’s interpretation show us his desire to make Islamic sharia as the highest independence ideology which supports people's lives in various aspects.